Exposure to and Knowledge of Media Messages on Exclusive Breastfeeding among Mothers in Three States in South-East Nigeria - Olanrewaju Abosede Mgboji; Michael O. Ukonu (Ianna Journal of Interdisciplinary Studies, 2024)
Background: Exclusive breastfeeding (EBF) involves providing only breast milk to respond to the infant's total nourishment needs within the first six months of life. Breast milk contains all the essential nutrients, antibodies, and other growth and development factors. EBF enhances an infant's immune system and vaccination response.